Design, synthesis and in vitro antiproliferative activity of new thiazolidinedione-1, 3, 4-oxadiazole hybrids as thymidylate synthase inhibitors. (1st January 2020) - Alzhrani, Zohor Mohammad Mahdi; Alam, Mohammad Mahboob; Neamatallah, Thikryat; Nazreen, Syed
Abstract: Thymidylate synthase (TS) has been an attention-grabbing area of research for the treatment of cancers due to their role in DNA biosynthesis. In the present study, we have synthesised a library of thiazolidinedione-1, 3, 4-oxadiazole hybrids as TS inhibitors. All the synthesised hybrids followed Lipinski and Veber rules which indicated good drug likeness properties upon oral administration. Among the synthesised hybrids, compound 9 and 10 displayed 4.5 and 4.4 folds activity of 5-Fluorouracil, respectively against MCF-7 cell line whereas 3.1 and 2.5 folds cytotoxicity against HCT-116 cell line. Furthermore, compound 9 and 10 also inhibited TS enzyme with IC50 = 1.67 and 2.21 µM, respectively. Finally, the docking studies of 9 and 10 were found to be consistent with in vitro TS results. From these studies, compound 9 and 10 has the potential to be developed as TS inhibitors.